Innovation, Quality Management and Competitiveness in the Food Processing Industry of Cameroon - Baninla Nicholas; Molem C. Sama; Nwahanye Emmanuel (European Scientific Journal, ESJ, 2023)
With the intensification of global and national competition, the focus of companies is on how to achieve competitive advantage. This led the foundation of studies on innovation and competitiveness but there are inconclusive results. In this light, this study was out to examine the mediating effect of quality management in innovation and competitiveness in the food processing industry of Cameroon. This study adopted the cross sectional research design for the investigation. The primary source of data was used for this study through the distribution of questionnaires to the respondents. Data was collected from 335 managers drawn randomly from a population of 2564 food processing companies operating in Cameroon. Inferential statistics was used during the analysis of the data specifically the Baron and Kenny’s approach of testing mediation hypothesis. Based on the results, there were traces of a positive and significant direct effects of product, process and organizational innovations on competitiveness. In terms of the indirect effect, there was the partial mediation of quality management in the effect of product innovation on competitiveness. While quality management had no mediating effect on other innovations (process, market and organizational) on competitiveness.